EQCM Analysis of the Process of Electrochemical Insertion in Regioregular Alkyl-Susbtituted Polyterthiophene during n-Doping. Issue 5 (24th May 2021) - Dini, Danilo; Salatelli, Elisabetta; Decker, Franco
Abstract : The material produced through the electrochemical polymerization of 3′4′-DDTT has been characterized with the EQCM during the process of n -doping. The supporting electrolyte (SE) was chosen considering mainly the two characteristics of hydrophobicity (to avoid the presence of water as potential contaminant) and chemical affinity with the alkyl and aromatic moieties present in poly-3′4′-DDTT. On these bases the salt ( n -C4 H9 )4 NClO4 was selected as SE since it contains the organic molecular cation ( n -C4 H9 )4 N + that is expected to represent the charge compensating species in poly-3′4′-DDTT during n -doping. The feature of the reversibility of the electrical current profiles originated by the process of injection/extraction of electronic charge carriers in poly-3′4′-DDTT, is not encountered in the associated EQCM data. The interpretation of the EQCM data requires the consideration of phenomena of different nature. In the present work a thorough discussion of the factors influencing the EQCM response during polymer n -doping is provided taking into account the spontaneous adsorption of cations, the eventual reorientation of poly-3′4′-DDTT on the substrate and the consequences of the chains rearrangement on the electrical polarizability of poly-3′4′-DDTT during the cycles of electrochemical n -doping and undoping.